2021
DOI: 10.3390/biomedicines9121775
|View full text |Cite
|
Sign up to set email alerts
|

Selective Anticancer and Antimicrobial Metallodrugs Based on Gold(III) Dithiocarbamate Complexes

Abstract: New dithiocarbamate cycloaurated complexes have been synthesized and their physicochemical and in vitro antitumor properties have been evaluated. All the performed studies highlighted good transport through the blood and biodistribution, according to the balance between the properties of hydrophilicity/lipophilicity and the binding of moderate strength to the BSA protein. Furthermore, none of the complexes exhibited reduction or decomposition reactions, presenting excellent physiological stability. The in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…The cytotoxicity of the human colon cancer cell line Caco-2/TC7 was evaluated in vitro , and complex 335 showed the best antiproliferative activity and excellent selectivity, with IC 50 values of 1.85 ± 0.36 μM for Caco-2/TC7 cells and 12.95 ± 0.11 μM for normal cells. 241 Khodjoyan et al synthesized and characterized several cationic gold( iii ) complexes with the general formula [(C^C)Au(N^N)]. The results showed that complex 336 (IC 50 = 0.12 ± 0.03 μM for A2780, 0.15 ± 0.01 μM for MCF-7, and 0.17 ± 0.03 μM for MDA-MB-231 cells) was particularly promising as this complex was more selective and active than cisplatin.…”
Section: Gold(iii) Complexes As Anticancer Agentsmentioning
confidence: 99%
“…The cytotoxicity of the human colon cancer cell line Caco-2/TC7 was evaluated in vitro , and complex 335 showed the best antiproliferative activity and excellent selectivity, with IC 50 values of 1.85 ± 0.36 μM for Caco-2/TC7 cells and 12.95 ± 0.11 μM for normal cells. 241 Khodjoyan et al synthesized and characterized several cationic gold( iii ) complexes with the general formula [(C^C)Au(N^N)]. The results showed that complex 336 (IC 50 = 0.12 ± 0.03 μM for A2780, 0.15 ± 0.01 μM for MCF-7, and 0.17 ± 0.03 μM for MDA-MB-231 cells) was particularly promising as this complex was more selective and active than cisplatin.…”
Section: Gold(iii) Complexes As Anticancer Agentsmentioning
confidence: 99%
“…ZnL1 had previously been demonstrated to have antiproliferative cytotoxic activity against TK10, UACC62 and MC7 human cancer cell lines with a IC 50 ranging from 14.28 to 22.74 µM 12 . It is not uncommon to observe that antitumoral compounds have some effect on bacterial pathogens 7 , 43 . However, experiments on animal models are needed to determine the exact range and efficacy of this compound, especially against biofilms.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that gold(III) complexes are well-known as cytotoxic agents, a balance between cytotoxicity and antimicrobial activity is crucial for the development of new gold(III)-based metalloantibiotics [ 11 ]. Despite many of the reported gold(III) complexes having a selectivity index in principle (that is, higher IC 50 values for the antiproliferative activity against cancer and human cells than the MIC values against bacteria), the therapeutic index usually needs to be increased by structural optimization [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%